(untitled) (Journal of Economic Research & Business Administration, 2025)
Meat industry’s significant multiplier effect on the economy is explained by the development of agriculture and feed production, logistics, and trade. Introduction of resource-saving and innovative technologies in the industry will contribute to improved product quality, reduced production costs and environmental impacts, and strengthen the competitiveness of meat products. The creation of new jobs will, consequently, lead to increased tax revenues. The accelerated development of the domestic meat industry will lead to reduced dependence on foreign markets, which will increase the economy’s resilience to external shocks, ensuring long-term and balanced growth. This article examines ways to improve the economic efficiency of regional meat processing plants, analyzes the current state of the industry, and identifies key issues related to insufficient productivity, high production costs, technological lag, and ineffective resource management. Sustainable development of meat processing enterprises in environment of imperfect competition requires a systems approach, including continuous assessment, monitoring, and modeling of enterprise resilience. Furthermore, key aspect is the integrated and comprehensive use of endogenous factors in production development. Effective strategic management requires the integration and coordination of the multifaceted activities of all enterprise divisions, which enhances flexibility and adaptation to changing economic conditions, minimizes the negative impact of external factors, and ensures the long-term competitiveness of the industry. This paper proposes methodology for assessing the economic efficiency of meat processing enterprises based on comprehensive analysis of production, financial, and marketing indicators. The methodological approach includes econometric modeling, SWOT analysis, and comparative analysis of industry best practices. Practical significance of this study lies in the development of proposals for enhancing enterprise competitiveness by reducing costs, improving product quality, and expanding sales markets. Findings and proposals presented can be used in strategic planning and management of meat processing enterprises, as well as in the development of state policy to support regional agribusiness. Key words: meat industry, animal husbandry, meat industry, meat products, meat processing industry, sustainable development, econometric assessment.